2019
DOI: 10.1063/1.5080079
|View full text |Cite
|
Sign up to set email alerts
|

The effect of particle size on the core losses of soft magnetic composites

Abstract: In the field of electrical machines, the actual research activities mainly focus on improving the energetic aspects; for this reason, new magnetic materials are currently investigated and proposed, supporting the design and production of magnetic cores. The innovative aspects are related to both hard and soft magnetic materials. In the case of permanent magnets, the use of NdFeB bonded magnets represents a good solution in place of ferrites. For what concerns the soft magnetic materials, the adoption of Soft M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 30 publications
0
6
0
Order By: Relevance
“…Various ferromagnetic powders can be coated with epoxy resin [124,125]. Particles size [20], resin content [126], and molding pressures [127] strongly impact the SMCs performances. In Pošković et al [126], the minimum epoxy content weight was strongly reduced to 0.05 wt.%.…”
Section: Epoxy Resinsmentioning
confidence: 99%
See 1 more Smart Citation
“…Various ferromagnetic powders can be coated with epoxy resin [124,125]. Particles size [20], resin content [126], and molding pressures [127] strongly impact the SMCs performances. In Pošković et al [126], the minimum epoxy content weight was strongly reduced to 0.05 wt.%.…”
Section: Epoxy Resinsmentioning
confidence: 99%
“…The granulometry of the powders [19,20] and the number of pores [21] in the final component are critical parameters in the SMC mixes. As for the latter, it is well known [22][23][24] that pores act as crack initiators.…”
Section: Introductionmentioning
confidence: 99%
“…The mechanical strength is dependent on fractions matching the medium and large particle sizes. Hybrid Magnetic Composites (HMC) [69][70][71] made of a mixture of soft and hard magnetic powder materials having a polymer binder provides mechanical strength and they are promising materials. HMCs are very small manipulative permanent magnets and can be used to replace AlNiCo and ferrite magnets.…”
Section: Magnetic Materialsmentioning
confidence: 99%
“…As a result of their use, the destruction the material's internal structure, resulting from the implementation of the mechanical laser cutting process (manifested by the deterioration of the material's magnetic prop ties), is avoided. Referring to additive manufacturing methods, a group of works descr ing research conducted on sintered materials can be identified [8][9][10][11][12][13][14][15], as well as a gro of works depicting the research results using laser powder bed fusion technology As the published research results on SMC and LPBF materials indicate, they can be us mainly in motors operating at frequencies of kHz and higher. Then, the low specific ir loss of the material about the Fe-Si laminates, which the authors of this article deal w Hence, there is a common interest in both the problem of the exact description of core losses and the search for methods to reduce them.…”
Section: Introductionmentioning
confidence: 99%
“…As a result of their use, the destruction of the material's internal structure, resulting from the implementation of the mechanical or laser cutting process (manifested by the deterioration of the material's magnetic properties), is avoided. Referring to additive manufacturing methods, a group of works describing research conducted on sintered materials can be identified [8][9][10][11][12][13][14][15], as well as a group of works depicting the research results using laser powder bed fusion technology [16][17][18][19].…”
Section: Introductionmentioning
confidence: 99%